An ultra‐long‐acting recombinant insulin for the treatment of diabetes mellitus in cats. (30th June 2021) - Gilor, Chen; Hulsebosch, Sean E.; Pires, Jully; Bannasch, Michael J.; Lancaster, Thomas; Delpero, Andrea; Ragupathy, Ramya; Murikipudi, Sylaja; Zion, Todd
Abstract: Background: Treatment of diabetes mellitus (DM) in cats typically requires insulin injections q12h‐q24h, posing a major compliance barrier for caregivers. Novel treatments enabling decreased injection frequency while maintaining safety are highly desirable. Insulin fused with feline immunoglobulin fragment crystallizable (Fc) has an ultra‐long plasma half‐life because it recycles through cells where it is protected from proteolysis. Hypothesis: Glycemic control can be achieved in diabetic cats with a recombinant fusion protein of a synthetic insulin and feline Fc (AKS‐267c) administered SC weekly. Animals: Five cats with spontaneous DM. Methods: Cats previously controlled using insulin glargine q12h were transitioned to once‐weekly injection of AKS‐267c. The dose of AKS‐267c was titrated weekly for 7 weeks based on continuous glucose monitoring. Clinical signs, body weight, fructosamine concentrations, and mean interstitial glucose concentrations (IG) were compared between baseline (week 0, on insulin glargine) and the last week of treatment. Data were assessed for normality and compared using parametric or nonparametric paired tests (as appropriate). Results: After 7 weeks of once‐weekly injections, compared to baseline, there were no significant changes in clinical signs, body weight (median [range] gain, 0.1 kg [−0.1 to +0.7]; P  = .5), fructosamine (−60 mmol/L [−338 to +206]; P  = .6), and mean IG concentrations (change = −153 mmol/L [−179 to +29]; P  = .3), and no adverse reactions were reported. Conclusion: Successful control of clinical signs and maintenance of glycemia was achieved with this once‐weekly novel insulin treatment. The efficacy and safety of this novel formulation should be further assessed in a large clinical trial.